Pengaruh Sanksi Pajak, Razia Lapangan, Sosialisasi Perpajakan, Samsat Keliling, Serta Pemberlakuan Program Pelayanan E-Samsat Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kota Mataram - Baiq Ugi Ediasari; Ida Ayu Nursanty; M. Wahyullah (Akuntabel: Jurnal Ilmiah Akuntansi, 2026)
This study aims to determine the effect of tax sanctions, field inspections, tax socialization, mobile Samsat services, and the implementation of the E-Samsat service program on the compliance of motor vehicle taxpayers in Mataram City. Taxpayer compliance is one of the key factors in supporting the optimization of regional tax revenue. This research used a quantitative method with a descriptive approach. Data were collected through a questionnaire distributed to 100 motor vehicle taxpayer respondents. The analysis technique used was multiple linear regression with the assistance of SPSS version 26. The results showed that partially, tax sanctions, field inspections, and the E-Samsat program had a positive and significant effect on taxpayer compliance. Meanwhile, tax socialization and mobile Samsat services had no significant effect on taxpayer compliance. Simultaneously, all five independent variables have a significant effect on taxpayer compliance, as evidenced by the F-statistic value of 14.13, which is greater than the F-table value of 2.31, with a significance level of 0.000 (<0.05). The Adjusted R Square value of 0.429 indicates that the five independent variables explain 42.9% of the variation in taxpayer compliance, while the rest is explained by other variables outside the research model.